Industrial specialisation, trade, and labour market dynamics in a multisectoral model of technological progress - Robert Stehrer (Johannes Kepler University of Linz, Department of Economics, 2001)
The issue of the impact of trade on specialisation structures and the effects of trade liberalisation on employment and labour markets has been intensively discussed in the recent literature on trade liberalisation and globalisation. In Europe this debate has gained new momentum in the discussion on the effects of the catching-up processes of the transforming economies in Eastern European Countries. But the bulk of the existing literature in this area employs almost without exception a static Heckscher-Ohlin framework based on factor-endowment differences and thus seems not to be a suitable tool for analysing dynamic issues of technology catching-up and dynamic adjustment processes. In this paper I present a model to explore the issue of productivity catching-up, international specialisation and labour market effects in a dynamic multi-sectoral framework with heterogenous labour. The model is basically an input-output model, but also has some Schumpeterian features. These Schumpeterian features are the impact of transitory rents, emerging from (labour) productivity-enhancing technological progress or catching- up processes, upon the price-, wage- and quantity system of the trading economies. Relative productivity and relative wage rate dynamics across sectors determine comparative cost advantages and trade specialisation. The second part of the paper presents some simulation studies of the evolution of prices, output, employment and wage structures, where various stylized types of technological progress and industrial catching-up processes are modelled. In the appendix of the paper the equilibrium solutions of the model are derived.
Keywords: C62; C63; C67; D57; F15; F17; 330; trade liberalisation; economic integration; labour markets; simulation; economic dynamics; growth; Außenhandelsliberalisierung; Arbeitsmarkt; Internationale Arbeitsteilung; Produktivität; Wirtschaftsmodell; Theorie; Makroökonomischer Einfluss